Recovery of long-term natural protection against reactivation of CMV retinitis in AIDS patients responding to highly active antiretroviral therapy - Di Perri, Giovanni; Vento, Sandro; Mazzi, Romualdo; Bonora, Stefano; Bonora, Adriana; Trevenzoli, Marco; Allegranzi, Benedetta; Carretta, Giovanni; Lanzafame, Massimiliano; Pizzighella, Sergio; Concia, Ercole (The Journal of infection, 1999)
Objectives: To see whether in severely immunosuppressed AIDS patients (with prior Cytomegalovirus retinal disease) who have significant increases in CD4+ lymphocytes following the initiation of highly active antiretroviral therapy (HAART) anti-Cytomegalovirus (CMV) maintenance therapy can be withdrawn with no subsequent progression of CMV retinitis. Methods: Eight patients with AIDS and one or more previous episodes of CMV retinitis interrupted anti-CMV maintenance therapy following the successful beginning of HAART. CD4 cell counts and HIV-RNA were monitored monthly while measurement of CMV antigenemia and ophthalmoscopy were carried every 2 weeks thereafter. Results: The HAART recipients in whom anti-CMV maintenance therapy had been interrupted had measureable increases of CD4+ T lymphocytes, substantial control of both HIV-RNA and CMV viraemia and did not show recurrence of retinitis during a mean follow-up of 98.4 weeks (range 78–120, SD 15.2). Conclusions: Anti-CMV maintenance therapy can be interrupted with no subsequent progression of retinal damage over a long time in patients with AIDS who successfully respond to HAART with a significant increase in CD4 cell count.